2020
DOI: 10.1126/scitranslmed.aay2140
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor-AB improves scar mechanics and vascularity after myocardial infarction

Abstract: Therapies that target scar formation after myocardial infarction (MI) could prevent ensuing heart failure or death from ventricular arrhythmias. We have previously shown that recombinant human platelet-derived growth factor-AB (rhPDGF-AB) improves cardiac function in a rodent model of MI. To progress clinical translation, we evaluated rhPDGF-AB treatment in a clinically relevant porcine model of myocardial ischemia-reperfusion. Thirty-six pigs were randomized to sham procedure or balloon occlusion of the proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 44 publications
1
49
1
Order By: Relevance
“…Once advanced heart failure occurs, a heart transplantation is the only option 4 . Regenerative therapies using live cells, proteins, and nuclei acids aims at altering the trajectory of adverse heart remodeling and promoting de novo cardiac repair [5][6][7][8] . However, it is difficult to deliver therapeutics to the heart, with high efficiency and low invasiveness and cost 9 .…”
mentioning
confidence: 99%
“…Once advanced heart failure occurs, a heart transplantation is the only option 4 . Regenerative therapies using live cells, proteins, and nuclei acids aims at altering the trajectory of adverse heart remodeling and promoting de novo cardiac repair [5][6][7][8] . However, it is difficult to deliver therapeutics to the heart, with high efficiency and low invasiveness and cost 9 .…”
mentioning
confidence: 99%
“…Our data from 3D imaging shows that delayed captopril treatment leads to higher vascular density in the infarcted heart border zone but has neither positive nor negative effect on vascular density in the infarct zone and in the posterior cardiac wall. Still little is known about the dynamic response of microvasculature to MI, although angiogenesis has emerged as a lucrative target in pharmacological research 15 , 16 , 60 . Captopril has been reported to inhibits angiogenesis in tumours 61 and skeletal muscle 62 , 63 , but no significant effect has so far been found on the angiogenesis in the infarcted heart 57 , 64 , 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our research group has reported the effects of a 7day recombinant human PDGF-AB (rhPDGF-AB) infusion in a clinically relevant porcine myocardial ischemia-reperfusion model. Compared with controls, rhPDGF-AB-treated animals exhibited increased infarct collagen anisotropy, maturation of collagen and increased vascular density (Thavapalachandran et al 2020). Functionally, this was associated with a 12% improvement in LVEF in the rhPDGF-AB group 28 days post-injury, decreased inducible ventricular tachycardia and a 40% reduction in arrhythmic mortality compared to the control group, which was mostly attributed to reduced infarct heterogeneity (Thavapalachandran et al 2020).…”
Section: Preclinical Testingmentioning
confidence: 99%